KUALITAS LAYANAN, CUSTOMER VALUE, DIGITALISASI BANK, KEPUASAN NASABAH DAN LOYALITAS NASABAH BPR - Wirantana, I Made Yogi; Adfi, Nyoman Rasmen (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.10.TAHUN.2022, 2022)
This study aims to determine the effect of service quality, customer value, bank digitization, customer satisfaction and customer loyalty of Rural Banks. The population in this study were all customers of PT BPR Lestari Bali. The sampling method used in this research is non-probability sampling with purposive sampling technique. The sample was obtained from the customers of 9 offices of PT BPR Lestari Bali. Instruments in data collection using a questionnaire measured by a 5-point Likert scale. This study uses an alternative structural equation modeling (SEM) method of PLS ??(Partial Least Square) with the SmartPLS 3.0 M3 program. The results of this study indicate that service quality, customer value, and bank digitization have a positive and significant effect on customer satisfaction. Service quality, customer value, and bank digitization have a positive but not significant effect on customer loyalty. Service quality has a positive and significant effect on loyalty mediated by BPR customer satisfaction. Customer value has a positive and significant effect on customer loyalty which is mediated by BPR customer satisfaction. Bank digitalization has a significant positive effect on customer loyalty through customer satisfaction. The presence of the customer satisfaction variable as a mediating variable is very important to increase customer loyalty.